STUDY OF THE OPERATING ELEMENTS DYNAMICS OF THE COTTON CLEANER (Scientific journal of the Fergana State University, 2023)
The article provides an effective constructive scheme of a cotton cleaner from large litter. On the basis of theoretical studies, patterns and graphic dependencies of the parameters of the operating elements of the cotton cleaner were determined. The analyses determined the recommended values of the parameters of the cleaner.